2014
DOI: 10.1016/j.stem.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Histone Variants Enriched in Oocytes Enhance Reprogramming to Induced Pluripotent Stem Cells

Abstract: Expression of Oct3/4, Sox2, Klf4, and c-Myc (OSKM) can reprogram somatic cells into induced pluripotent stem cells (iPSCs). Somatic cell nuclear transfer (SCNT) can also be used for reprogramming, suggesting that factors present in oocytes could potentially augment OSKM-mediated induction of pluripotency. Here, we report that two histone variants, TH2A and TH2B, which are highly expressed in oocytes and contribute to activation of the paternal genome after fertilization, enhance OSKM-dependent generation of iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
151
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 49 publications
5
151
0
2
Order By: Relevance
“…Nucleosomes containing hyperacetylated histones are thought to be more prone to displacement by protamines (Oliva et al, 1987). These previous reports are consistent with the observations that TH2A and TH2B, which induce an open chromatin structure (Shinagawa et al, 2014), are required for the replacement of histones by TNPs. However, we cannot exclude the possibility that such defects are due to a decrease in the total histone level, because canonical histone H2A and H2B underdosage leads to defective meiosis in yeast (Hanlon et al, 2003).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nucleosomes containing hyperacetylated histones are thought to be more prone to displacement by protamines (Oliva et al, 1987). These previous reports are consistent with the observations that TH2A and TH2B, which induce an open chromatin structure (Shinagawa et al, 2014), are required for the replacement of histones by TNPs. However, we cannot exclude the possibility that such defects are due to a decrease in the total histone level, because canonical histone H2A and H2B underdosage leads to defective meiosis in yeast (Hanlon et al, 2003).…”
Section: Introductionsupporting
confidence: 92%
“…Male homozygous mutant mice lacking both Th2a and Th2b genes are sterile (Shinagawa et al, 2014). The testis and epididymis of 3-month-old mutant mice showed a 28% and 17% reduction in weight, respectively, compared with the controls (Fig.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This transformation is associated with modifications in chromatin structure and in cellular phenotype through an intricate network of transcription and epigenetic factors driving the dynamics required for the generation of induced pluripotent stem cells (iPSCs). Different epigenetic modulators -including histone-modifying enzymes such as Dot1L (Onder et al, 2012), chromatin remodelers such as Chd1 (Gaspar-Maia et al, 2009) and histone variants -have been implicated in the regulation of reprogramming (Shinagawa et al, 2014;Gaspar-Maia et al, 2013). Histone metabolism is governed by histone chaperones (Avvakumov et al, 2011) such as Asf1a, Nap1, Caf1, which also assist in different nuclear processes including repair, replication, transcription and could modulate the post-translational modification of histones (Kim and Haber, 2009;Quivy et al, 2008;Sharma and Nyborg, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adding active small molecules that are associated with epigenetic modification, such as VPA (Huangfu et al, 2008), DNA methylase inhibitors (Huangfu et al, 2008;Mikkelsen et al, 2008), histone methylase inhibitors , histone deacetylase inhibitor (Hai et al, 2011), protein arginine methyltransferase inhibitor (Yuan et al, 2011), or vitamin C (Esteban et al, 2010), has been reported to be able to increase the iPSCs reprogramming efficiency. Similar to nuclear transfer, some maternal factors, such as TH2A and TH2B (Shinagawa et al, 2014), can promote iPSCs reprogramming. Also, the activity of endogenous retrovirus HERVH was shown to have connection with pluripotency of human iPSCs (Ohnuki et al, 2014).…”
Section: Overexpression Of Transcription Factorsmentioning
confidence: 99%